The Level of Including Jurisprudence of Reality inIslamic Education Textbooks for the Secondary Stage in Jordan - Al-Jazi عبدالله علي داغش (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
The study aimed to identify the level of including jurisprudence of reality in Islamic education textbooks for the secondary stage in Jordan. The study sample consisted of Islamic education textbooks for the secondary school grades in Jordan in the academic year 2020/2021. To achieve the objectives of the study, a list of issues of jurisprudence of reality was prepared, including six main areas, under each of which falls a set of issues of jurisprudence of reality. In the light of these issues, the textbooks were analyzed after checking its sequometry properties. The most prominent results were that the textbooks of Islamic education for the secondary stage in Jordan included (166) occurrences of issues pertinent to the jurisprudence of reality issues in their content, The highest rate of the jurisprudence of reality reported was in the (cultural, intellectual and mathematical) area. The number of the occurrences for this are reached ( 67), with a percentage of 40%, while the lowest reported rate was for the area of (worship), which recorded approximately (7) occurrences, with an approximate percentage of (4%). The study recommended the need for balance in distributing jurisprudence of reality issues in Islamic education textbooks for the secondary stage